Barriers to Exercise in a Medical Unit of US Army Reservists: An Exploratory Study - Madelyn B Huhn; Elizabeth A Kleitz; Namuna Sunar (Undergraduate Research Journal for the Human Sciences, 2023)
Military Reservist healthcare workers must meet physical fitness standards similar to those on active duty. They, however, experience a unique occupational environment as citizen Soldiers. Their civilian careers as healthcare workers and their positions in the military both demand shift work, long hours, and critical response to high stress events. For a small group of Reservists working in civilian healthcare occupations who also serve in medical roles in the military, this exploratory study aimed to describe any perceived barriers to exercise. Although over 60% of respondents to an exercise barriers scale perceived physical and social health as the top benefits of exercising, a similar proportion viewed lack of time, time away from family, and financial cost as barriers that most interfered with their ability to exercise. Time and access to exercise, though, are imperative for mission readiness. Respondents may be at risk of not obtaining adequate exercise for optimal physical fitness.
Keywords: Exercise; Physical activity; Health Behaviors; Military; Medical